Integration of Ecotourism Development and Edutourism in the Airlangga Park area of Pataan Temple (Study in Pataan Village, Sambeng District, Lamongan Regency) - Mochammad Afif; Nurul Badriyah; Titin Titin; Rivatul Ridho (Jurnal Akuntansi dan Pajak, 2023)
The excavation of the fifth stage by the Arceolong Agency of BPCB East Java explained that Pataan Temple was a historical heritage site of the Airlangga Kingdom. The integration of ecotourism development aims to introduce other tourist areas that are more interesting to visit when coming to Pataan Temple. The method used is Digitalization Integration which prioritizes the Wild Zone (very natural), from the mapping results to be entered into digital applications there are 30 tourist areas including Tegal Duwur Hill, Mahogany Forest, Dukun Jurang, Pebble Hill, Magersari Village, Ngadasan Hill, Sanglit Forest, Godan Hill, Kendil Hill, Ngadosan springs, Wuluh Springs, Moncor Springs, Lanang Springs, Amata Springs, Selegreng Springs, Balan Springs, Kulon Springs, Dringu Kidul Springs, Dringu Lor Springs, Telogo Springs, Telogo Watu, Airlangga Tourism Park, Keywords: Integration, Ecotourism, Edutourism, Digital Applications